The Workload Impact on Healthcare Workers At The Hospital In Covid-19 Era: A Systematic Review - Azwar Azwar; Ilyas Y; Alrianti Alrianti; Marlina Marlina; Ridho Ridho (Journal Research of Social Science, Economics, and Management, 2023)
COVID-19 has been declared a worldwide pandemic by WHO on 11th March 2020. The aim of this study was to collect data and investigate across the world in dealing with the load of healthcare workers on their healthcare systems to get a better understanding of the real difficulties and challenges they faced. This study is a systematic review, searched some literatur of PUBMED, PROQUEST, OXFORD JOURNAL, WILEY JOURNAL and SCOPUS journal databases published in 2020. We used the keywords; “Workload” and “healthcare workers” and “COVID-19”, and screened by inclusion and exclusion criteria. Nine studies have screened from 673 articles from database, which investigated factors independent of the workload of the healthcare workers and explaining the strategy of hospitalis in overcoming the healthcare workers workload in COVID-19 era. We found several factors related to the workload of health workers in the COVID-19 era: using the PPE, lack of knowledge about disaster management, the type of professional group, increasing the number of COVID-19 patients and the rapidly progress of patient severity. Changing the flow of patient services is one of pursuing a strategy to reduce the workload by put the screening at the first step of patient arrival to the hospital.